2020
DOI: 10.1007/s40195-020-01042-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Corrosion Resistance of a Biodegradable Mg–Y–Zn Alloy with LPSO Phases via Multi-pass ECAP Process

Abstract: Mg-RE (rear earth) alloys with long period stacking (LPSO) structures have great potential in biomedical applications. The present work focused on the microstructure and corrosion behaviors of Mg 98.5 Y 1 Zn 0.5 alloys with 18R LPSO structure after equal channel angular pressing (ECAP). The results showed that the ECAP process changed the grain size and the distribution of LPSO particles thus controlled the total corrosion rates of Mg 98.5 Y 1 Zn 0.5 alloys. During the ECAP process from 0p to 12p, the grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…However, for Mg alloys, it is difficult to refine the grain size to submicron grains with the increase of the pass. Wang et al showed that the grain size decreased from 160-180 µm to 6-8 µm after twelve passes at 380 • C for Mg alloys with long-period stacking structure [61], Jiang et al reported that ultrafine equiaxed grains of 2.5 µm were obtained after sixteen passes via route A at 603 K [62]. Ma et al found that the grain size of Mg alloys decreased from 80 µm to 1.5 µm after thirty-two passes at 603 K [63].…”
Section: Grain Size From 01-1 μMmentioning
confidence: 99%
“…However, for Mg alloys, it is difficult to refine the grain size to submicron grains with the increase of the pass. Wang et al showed that the grain size decreased from 160-180 µm to 6-8 µm after twelve passes at 380 • C for Mg alloys with long-period stacking structure [61], Jiang et al reported that ultrafine equiaxed grains of 2.5 µm were obtained after sixteen passes via route A at 603 K [62]. Ma et al found that the grain size of Mg alloys decreased from 80 µm to 1.5 µm after thirty-two passes at 603 K [63].…”
Section: Grain Size From 01-1 μMmentioning
confidence: 99%
“…It is worth mentioning that the method of production and its parameters also influence the corrosion resistance of Mg-LPSO alloys. As reported by Wang et al [24], the number of passes during equal channel angular pressing (ECAP) has a major effect on the corrosion resistance of Mg-1Y-0.5Zn; however, there is no straightforward dependence showing that with the increasing number of ECAP passes, the corrosion resistance increases.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, they also demonstrate superior abilities to accelerate the osseointegration rate, enhance bone healing and prevent the biofilm formation [1][2][3][4]. More importantly, they have outstanding biodegradability, and their degradation products can promote the growth of new bone [5][6][7][8][9][10][11][12][13][14]. Thereby, they are deemed as promising orthopedic alternatives to traditional metal implants, such as 316L stainless steels, Ti6Al4V alloys and cobalt-chromium-based alloys [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%